HSCT FOR NON-HODGKIN LYMPHOMA - Baldissera, Renata; Hallack Neto, Abrahão Elias; Castro, Renato; Perrini, Guilherme; Silva, Leandro de Pádua; Chiattone, Carlos (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION